Visual representation of students’ experience : alternative assessment during COVID-19 Movement Control Order - Cheah, Whye Lian; Ayu Akida, Abdul Rashid; Helmy, Hazmi; Law, Leh Shii (UNIMAS Publisher, 2023)
The recent COVID-19 Movement Control Order has driven the need adopt an innovative approach in conducting assessment that exclude face-to-face interaction. For MDP30609 Community Medicine and Public Health posting, the assessment has been modified by adopting the Alternative Assessment method. The Alternative Assessment is regarded as comprehensive, where it assesses the candidates’ ability to integrate writing task and performance, divergent thinking in solving problems and enhancement of meaning skills. In addition to presenting a research proposal and drafting a journal manuscript for publication, a group of year three medical students were asked to produce a comic on the prevention of COVID-19 aimed at primary school children in a rural community. Through comic production, the students can use it as a learning tool that foster empathy, cultivate awareness towards social issues and strengthen observational skills – of which, are all relevant skills in medical training. The other main goals are to encourage students to self-reflect, embrace creativity, improve their communication skills through visual storytelling, and more importantly, to shape their professional identity as future medical doctors.